HOW STANDARDS ‘TRAVEL AND CHANGE BETWEEN CONTEXTS: NATIONAL STANDARDS FOR TVET TEACHER EDUCATION IN THE UK - Lucas, Norman (UPI Press, 2012)
This paper focuses on the development and growth of standard-led reform and regulation of TVET teachers and trainers in the UK by developing a theoretical discussion and critique of standards that has a wider relevance to that in other countries. It shows how standards-led regulation in the UK has moved from a permissive to a more rigid approach where new standards have been defined. The study also illustrates how standards are mediated and interpreted differently within the diverse contexts and communities of practice by developing a critique of the standards-led model, an attempt to codify both situated and non-situated knowledge. Here, standards are treated as decontextualised, vertical knowledge simply applicable across diverse contexts, subjects/vocational practices, learning in the workplace and training TVET teachers. Within the diverse practices of TVET teachers and teacher educators, different types of understandings exist and different types of knowledge and pedagogy are learnt, used and transformed. Not only do attempts to deal with the complex zone of professional practice by standards fail to address the inherent ambiguity of standards, but also lead to a bureaucratic, competency-based framework which marginalizes professional knowledge and understanding.Â Keywords: TVET teachers and trainers, standard-led reform and regulation, professional knowledge